Assessment of Kisan Mobile Advisory (KMA) Service for Dissemination of Agricultural Information in Mehsana District of Gujarat State - M. R. Patel , M. V. Patel and R. A. Patel, (Indian Journal of Extension Education, 2017)
In present scenario, agriculture being highly skill oriented technically intensive needed a high priority. At present theratio of farmers to extension worker is quite low (1000:1). Maximum RAEO or other extension workers disseminatedagriculture knowledge without having much accountability and expertise. This issue has created a gap between improvedagriculture technology and the end user (farmer). To address the issue Kisan Mobile Advisory Service was launched forsending information through SMS in Mehsana District through Krishi Vigyan Kendra during January 2014. The contentof messages were typed in Gujarati language and information related to crop production, crop protection, vegetable andfruit production, spice crops, dairy farming, weather forecasting, post harvest management and other agricultural andallied related information sent to end users. To evaluate and information and usefulness of information, the present studywas conducted with survey of 80 farmers, 10 in-service personnel and 10 input suppliers of district during 2014-15. Theresult of survey shows that messages were highly understandable for majority (42.50 %) of the farmers. It was highlyunderstandable for 80 per cent and 50 per cent KMA member of in-service personnel and input supplier category,respectively. The messages were needful and timely for 67.50 per cent of KMAmember of farmers’category and about 70per cent and 50 per cent for in-service personnel and input supplier, respectively. As far as applicability of message isconcerned, messages were fully applicable for about 44 per cent of KMAmember of farmers’ category whereas mediumand partially applicable were reported by 17.50 per cent and 22.50 per cent of members, respectively. It was also foundthat messages were fully applicable for in-service personnel (60 %) and input supplier (50 %). Majority of the farmers(72.50 %) conveyed the messages minimum to at least another farmer in social system